Can constitutions or laws change marriage? : Reflections on the "Goods of marriage" and natural law of John Finnis - Savić, Vanja-Ivan (Array, 2019)
In this article the author examines recent case of the US Supreme Court Obergefell v. Hodges in which group of academics acted as amicus curiae in explaining natural law grounds for having traditional approach to marriage as a union between one woman and one man. Author shows connection between teachings of natural law legal theorist John Finnis and his work named 'Goods of marriage' and requests for keeping 'the marriage' reserved only for heterosexual couples. Heterosexual marriage, according to Finnis, protects the family, the Judeo-Christian concept of monogamy, and other social values that we have reached through social evolution.